Analisis Pengurangan Waste pada Proses Produksi Papercore Menggunakan Metode Six Sigma DMAIC (Studi Kasus: PT. XYZ) - Abdullah Hudan; Wiku Larutama (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
This study aims to analyze and minimize waste in the papercore production process at PT. XYZ using the Six Sigma DMAIC methodology. The main problem identified is a high waste level reaching 13.67% of total production, equivalent to 102,257 kg in December 2025. The research was conducted through the Define, Measure, Analyze, Improve, and Control stages, utilizing Pareto diagrams and fishbone analysis as analytical tools. The results indicate that the Winding process is the largest contributor to waste, with Winding 1 accounting for 28% of the total waste. The root causes of waste originate from Man, Machine, Method, and Material factors. Improvement proposals focus on enhancing SOP compliance, operator training, implementing preventive maintenance, and strengthening material quality control. The application of the DMAIC approach is expected to reduce waste levels and improve production process efficiency in a sustainable manner.